Low-level biological dosimetry of heterocyclic amine carcinogens isolated from cooked food. - Turteltaub, K W (1993)
The bioavailability and the bioreactivity of the carcinogenic heterocyclic amine [2-14C]2-amino-1-methyl-6-phenyl-imidazo[4,5-b]pyridine (PhIP) have been investigated at a dose approximating that likely from the human diet by accelerator mass spectrometry (AMS). [2-14C]PhIP was administered to mice at a dose equivalent ot the consumption of two 100 g beef patties (41 ng/kg). The biological half-life of PhIP was 1 hr, with 90% of the dose being excreted via the urine. Peak tissue PhIP concentrations were reached within 3 hr, with the highest levels in the tissues of the gastrointestinal tract, followed by the liver, kidney, pancreas, and thymus. Since the detection limit by AMS is dependent on the natural abundance of 14C, we have achieved further increases in sensitivity by producing mice that have 20% of the natural abundance of 14C. Use of these 14C-depleted animals allows measurements to be made near the natural level of exposure for many environmental carcinogens. PhIP-DNA adduct levels have also been measured by 32P-postlabeling at doses of 1.0, 10, and 20 mg/kg. The highest adduct levels were found in the pancreas, thymus, heart, and liver and increased linearly with dose. The principal adducts are derived from guanine.